Academic Achievement, the Labor Future and Inequality - Cecilia Braslavsky; Gustavo Cosse (Universidad Autónoma de Madrid, 2018)
"The negative" inequalities are associated to a series of processes that began a long time ago : i) the diminution of the necessary work for the production of goods and services required for the satisfaction of the basic necessities of the world-wide society; ii) the change in the phantom of the existing formal works and its duality between works in which technical progress is introduced, on one hand, and others very mechanized, iii) the accelerated changes in the profiles of the occupations, iv) the acceleration of the processes of labor relaxation and the consequent more and more intense separation between the formal works and the nonformal ones by a side and between work protected and not protected by another one and v) the modification of the scales in which the labor destiny of the people is made and solved, with the exacerbación of the inequalities in the labor possibilities according to is internationalized "or" not internationalized "profiles". Different groups are particularly affected by that set of this processes. In first term, the originating immigrants of poor countries towards richer countries are in the greater risks. On the other hand, the poor young people of original groups of the receiving countries also feel in defenselessness situation. In front of this incomplete set of questions that form thus the call "society of risk" is reanimated to the debate respect to the equality or the fairness, in general, and of the educative fairness, in individual. Original reference: Braslavsky, C. y Cosse, G. (2003). Los logros académicos, el futuro laboral y la equidad educativa. Ponencia presentada en la Universidad Autónoma de Barcelona, Febrero de 2003.